(3QhVI GdCRgGQ aj Yde hbJ Gddjd hGdfgGQs - (3CHh RjO YHO GdQMef Hf CHj ZGdH Hf YHO GdQMef GdJLjHj GdLGOQjs
(3ChdgG (B:s
(3GdMeO ddg GdYRjR GdbGOQ echQ Gddjd GdMcje GdbGgQ hHYO aGYde Cf Yde GdhbJ ef CcHQ GdYdhe cd hbJ dCfg aQV Ydi GdCYjGf hdjdg ef ChVM GdHQgGf s
(3BNQgG (B:s
(3hgGgfG Ke GdPi fXeJ ef Yde GdChbGJ ceG CQOJ SfI CQHY hJSYjf eVJ ef HYO SHY eFI bO EfbVJ hGdMeO ddg Ydi eG CfYeG Ydi ef GdBjI hCdgeG ced HMeO Gddg s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B106s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B592 ; (3HQhcdeGf (B- (3GdLRA (B2 - (3U (B168 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B217 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3Gdadcs